The Sound of William Barnes's Dialect Poems: 2. Poems of Rural Life in the Dorset Dialect, second collection (1859) - Burton, T. L. (University of Adelaide Press, 2017)
"This is the second volume in a series that sets out to provide a phonemic transcript and an audio recording of each individual poem in Barnes's three collections of Poems of Rural Life in the Dorset Dialect. Beginning with two poems that inspired Vaughan Williams to set them to music, and ending with a paean of praise for the poet's native county, this second collection contains 105 poems of immense range and power. There are poems of longing, love, and loss; pain and protest; tears and laughter; grief and consolation; feasting and celebration; music and birdsong; falsehood, friendship, and faith; generosity and meanness; bad temper and good; stasis and travel; flowers and trees; storm and calm. "Here," as Dryden said of Chaucer's poems, "is God's plenty"."